Plasma concentrations of endothelial nitric oxide synthase (enos) after different physical exercises - E. Yu. Dyakova; L. V. Kapilevich; A. N. Zaharova; A. V. Kabachkova; T. A. Kironenko; S. N. Orlov (Бюллетень сибирской медицины)
The purpose of the study is to evaluate the effect of dynamic and static exercises on eNOS concentrations in the blood plasma of athletes who do cyclic and strength kind of sports, as well as in men, who are not involved in any sports.Materials and methods. Determination of plasma concentrations of eNOS was performed by using enzyme immunoassay. Blood samples were collected from weightlifters and track and field athletes before and after static and dynamic exercises.Results. It has been shown that regular exercises contribute to a significant increase in the background level of endothelial nitric oxide synthase (eNOS) in the plasma of athletes. It is necessary to note that eNOS is almost twice higher in the weightlifters than in the track and field athletes. eNOS concentrations significantly decrease in athletes after static exercises , but on the contrary, increase after dynamic exercises. eNOS level rise in untrained individuals occurs after all kinds of exercises, although the influence of dynamic exercises is much more pronounced. Plasma concentrations of eNOS in all groups returned to baseline during the recovery period.These results suggest that the underlying mechanism that regulates the amount of eNOS in the plasma during exercises is associated with vascular factors, first and foremost, with the intensity of regional blood flow and its impact on the endothelium surface. Therefore, this protein cannot be positioned as a representative of a myokine group.